ARTIFICIAL INTELLIGENCE: OPPORTUNITY AND THREAT - Dovranova Mokhidil (Web of Journals Publishing, 2025)
Artificial intelligence, so AI, is currently in trouble with opportunities and threats. Although the capabilities of artificial intelligence have been very wide, there are also threats in managing it and using it for other areas. For example, artificial intelligence can develop in its self-updating and learning abilities, but it is necessary to regulate it in relation to the problems of ethics, security and confidentiality. For such reasons, its threats also grow when the development of artificial intelligence continues. This article explores the implications of artificial intelligence as an opportunity or threat and its own differing effects on family relationships.
Keywords: Artificial intelligence, industrial revolution, homo sapines, opportunities and threats, family culture, youth education, social sphere, social engineering, information security.